Influence of SiO2 nanoparticles additive on radiation stability of TiO2 micropowders; International Workshop Radiation Effects in insulators and non-metallic materials, Астана, June 2-4, 2014 - Sazonov R. V. Roman Vladimirovich; Kholodnaya G. E. Galina Evgenievna; Ponomarev D. V. Denis Vladimirovich; Remnev G. E. Gennady Efimovich; Mikhaylov M. M.; Yurjev S. A. (2014, 2014)
В фонде НТБ ТПУ отсутствует